In vitro fertilization‐induced pregnancies predispose to gastroesophageal reflux disease. Issue 2 (1st April 2016) - Turan, Ilker; Kitapcioglu, Gul; Tavmergen Goker, Ege; Sahin, Gulnaz; Bor, Serhat
Abstract : Background: Women conceiving following in vitro fertilization (IVF) likely have a variety of risk factors that predispose them to gastroesophageal reflux disease (GERD) in the future. Objective: We aimed to investigate whether pregnancy through IVF may predispose to subsequent GERD compared with pregnancies without IVF. We also evaluate whether twin IVF pregnancies lead to additional risk for having GERD compared with singleton IVF pregnancies. Methods: A validated reflux questionnaire was administered to 156 women with singleton ( n  = 102) or twin ( n  = 54) IVF birth (IVF group) and 111 women with a naturally conceived singleton birth (control group). All women included in the study were primiparas who had given birth at least 1 year prior to data collection. The diagnosis of GERD was based on the occurrence of typical symptoms (heartburn, regurgitation, or both) at least once a week. Results: The prevalence of GERD was 13.5% and 4.5% in IVF and control groups ( p  = 0.015); in the IVF group, this was slightly higher, but not statistically significant, in women with twin compared with singleton pregnancies (14.8% vs. 12.7%, p  = 0.749). Logistic regression analysis showed that IVF was strongly associated with subsequent GERD (OR, 3.30; 95% CI 1.20–9.04; p  = 0.02). Conclusion: The risk of developing GERD at least 1 year after delivery increased following IVF. Long‐term follow‐up studies are required to determine whether therapy during pregnancy can prevent this risk.